Urban Temperature Profiles and Land Cover Detection in the Jakarta Metropolitan Area using Remote Sensing - Hasti Widyasamratri; Kazuyoshi Souma; Tadashi Suetsugi (Faculty of Geography, Universitas Gadjah Mada, 2019)
This research aim to investigate the urban thermal environment profile and land cover classification in the Jakarta Metropolitan Area (JMA) in 1989 and 2013. Thermal environment conducted by installing fix point ground measurement of air temperature and land surface temperature. The land cover classification was carried out by using Landsat TM 5 and Landsat 7 ETM+ data sets. The diurnal variation of air temperature shows that Urban Heat Island (UHI) was occurring in urban and suburban JMA, which can be seen the slower cooling period in the urban area than suburban areas. Positive correlation between air temperature (Ta) and land surface temperature (Ts) on the brush (r2 = 0.78) and the asphalt surface (r2= 0.88) is clearly shown during the study. The rapid urbanization was detected during 1989 to 2013 where the urban sprawl is spread over to the whole area of JMA. Urban built up is the dominant of high increase due to years, while vegetation is decreasing.